The Impact of Interethnic Marital Relation on the Dynamics of Interdependence: A Phenomenological Finding from Javanese and Chinese Couples in Indonesia - Yulianto, Jony Eko; Faturochman, Faturochman (UI Scholars Hub, 2016)
Javanese and Chinese Indonesians (Tionghoa) ethnicity both emphasize the importance of social harmony in their relations. Does it exist in intermarriage of these two ethnics? The present study describes the existence of interdependence and its dynamics in the marital relation between Chinese Indonesian women and Javanese men by applying qualitative method with phenomenology approach on 24 married couples in Solo and Yogyakarta. The result shows that interdependence manifestation in interethnic marriage includes identity establishment, the use of power, and the utilization of resources. Identity establishment consists of fused identity, layered identity, attributed identity, and value-focused identity. The use of power exists in variations of hierarchy, domination, and versatile. The utilization of resource shows the variations of communal-sharing, transaction, and domination. Interdependence dynamics between husband and wife manifest in interpersonal level which emphasizes the role of trust and distrust, intrapersonal level which is expressed in affection toward spouse, transcendetal level which is voiced in the role of trust toward transcendental agents, and intergroup level which is pointed to role of meta-relational model of extended family.